Pengembangan E-Modul Berbasis Inkuiri Terbimbing Terintegrasi Laboratorium Virtual Pada Materi Sistem Koloid Kelas XI SMA atau MA - F Febriyandi; Andromeda Andromeda (Universitas Negeri Padang, 2019)
The type of research used is research and development or Research and Development (R and D). The development model used is a 4-D model (four-D models) which consists of 4 stages, namely: define, design, develop and disseminate. This research is limited to the stage of development, namely the validity and practicality test. The research instrument used was a questionnaire of validity and practicality. The e-module was validated by 6 validators while the practicality test was carried out by 2 chemistry teachers and 20 XI grade students of MIPA SMAN 12 Padang and 20 XI grade students oh MIPA SMAN 2 Pariaman. Data from the validity and practicality test results were analyzed using the cohen kappa formula. Based on the results of the study, it was found that the average kappa moment of validity test was 0,87 with a very high validity category and the average kappa moment of teacher practicality was 0,88, students of SMAN 12 Padang were 0,87 and students of SMAN 2 Pariaman were 0,88 with a very high practicality category. Thus, it was concluded that acid base e-module based on discovery learning was produced for valid and practical high school students.